(untitled) (Global Journal of Medical Research, 2016)
Background: Mycobacterium Tuberculosis (TB) has been an important cause of mortality and morbidity all over the world but is specifically affecting developing countries like India where the disease is endemic. Inspite of being asymptomatic, female reproductive system is found to be very vulnerable to tubercular infections and by the time, Nontuberculous mycobacterial infections are also emerging and are found to cause serious genital infections in the females of child bearing age leading to infertility. Objectives: Detection of Mycobacterial (MTB